Design thinking the handbook - Uebernickel, Falk 1979-; Jiang, Li; Brenner, Walter 1958-; Pukall, Britta 1965-; Naef, Therese; Schindlholzer, Bernhard 1982- (World Scientific, 2020)
"Design thinking is more than just a new, one-off method of innovation. Its focus is on establishing an innovation-friendly climate in companies and organizations for the long-term. To achieve this, an interdisciplinary team of authors has composed this "recipe book" that can be practically applied to your everyday business life. This book is for all who intend to understand and practice the design thinking method in the most rapid and uncomplicated way. The first part describes in depth what this method is all about. The second part of this comprehensive book offers you a step-by-step guide to practically apply design thinking. The subsequent sample cases show how to put theory into practice. The authors have gained their expertise in design thinking from both academic and scientific theory, and from countless long-term implementations at companies in various industries. So, benefit from this rich knowledge and start becoming innovative today. This book will show you how it's done"--Publisher's website